Assessing the role of tryptophan supplementation in enhancing growth, reducing aggression, and boosting immunity in juvenile Scylla paramamosain - Wenping Feng; Zeping Zhao; Hanying Xu; Xueting Liu; Tao Han; Jiteng Wang (Aquaculture Reports)
This study aimed to establish the optimal dietary tryptophan (Trp) level for juvenile mud crab Scylla paramamosain and evaluate its effects on growth, aggressive behavior, and immunity. A 56-day feeding trial was conducted using five diets with Trp levels of 2.94, 3.38, 3.68, 4.05, and 4.39 g kg−1 (dry diet), respectively. The results showed that Trp supplementation of 3.68 g kg−1 maximized the growth, and significantly increased protein content, aromatic amino acid levels, digestive enzyme activity, and the expression of protein synthesis-related genes (Tor and S6k1) (P < 0.05). The diet with 4.05 g kg−1 of Trp reduced aggressive behavior (P < 0.05), which resulted in increased serotonin levels (P < 0.05), suggesting that Trp can be metabolized into serotonin in vivo to suppress aggression. However, further increases in Trp levels negatively affected trypsin and lysozyme (P < 0.05), indicating potential adverse effects of excess Trp on juvenile crab health. Quadratic polynomial regression analysis, using weight gain rate (WGR) and specific growth rate (SGR) data, suggested that the optimal dietary Trp supplementation range is 3.94–3.98 g kg−1 for juvenile S. paramamosain. These results provide valuable insights for formulating diets in crustacean aquaculture, which can improve growth performance and support animal welfare of juvenile mud crabs.